Photocurrent conversion efficiency of TiO2 nanotube photoanodes in dependence of illumination intensity - Denisov, Nikita; Zhou, Xin; Cha, Gi; Schmuki, Patrik (Electrochimica Acta, 2021)
In the present work, we investigate the photoresponse of TiO2 nanotube photoanodes as a function of the illumination intensity and compare it to compact anodic TiO2 layers. While for the compact layers, in line with expectations, the IPCE is virtually independent of the light intensity, we find for the nanotube morphology a significant increase in the magnitude of the IPCE with lowering the illumination intensity. Moreover, for low light intensities a noticeable change in the IPCE spectra, a substantial slowdown of the transient photocurrent kinetics, an increase of the charge transport time constants, and an anodic shift of the optical flat-band potential is observed. We attribute the sensitivity of the IPCE and other photoresponse effects mainly to a hole accumulation and trapping caused by higher illumination intensities – this effect is particularly strong due to the geometry of the tubes. The observed effects have significant implications for the interpretation and comparability of the TiO2 NT photocurrent data.
CRIS-Team Scopus Importer:2021-03-19
Keywords: IMPS; IPCE; Mott-Schottky analysis; Photoelectrochemistry; TiO2 nanotubes